Students’ Perception of The Talking Stick Technique in Enhancing Students’ Speaking Skills - Putri, Putri Amanda; Apriyanti Hasibuan; Sartika Dewi Harahap (CV. Ulil Albab Corp, 2025)
This study investigates students’ perceptions of the Talking Stick technique in enhancing English-speaking skills among seventh-grade students at MTsN 4 Mandailing Natal. The technique was implemented as an alternative teaching strategy to promote active, confident, and motivated speaking participation. This research applied a descriptive qualitative method supported by quantitative data. Data were collected from 32 students of class VII-J through observation, questionnaires, interviews, and documentation. The findings showed that students’ perceptions toward the Talking Stick technique were dominantly positive, with a mean percentage of 89.7%, indicating a very high level of positive response. Students agreed that the technique made English learning more enjoyable (100%), improved confidence (91%), and reduced fear of making mistakes (78%). Furthermore, it significantly increased students’ motivation and self-confidence, with an average score of 90.6%. However, several challenges remained, including nervousness when speaking (68.8%), limited vocabulary (78.2%), and grammatical concerns (71.9%). Overall, the Talking Stick technique effectively enhanced students’ speaking participation, confidence, and classroom interaction. It is recommended that English teachers use this strategy to create an interactive and supportive learning environment that fosters students’ communicative competence.